Compliance with the breakthrough cancer pain European guidelines and impact on patients' quality of life: an observational prospective study - Bossi, Paolo; Pietrzyńska, Tatiana; Margarit Ferri, César; Mansilla, Irene; Tellone, Valeria; Fioravanti, Sara; Di Loreto, Giorgio; Comandini, Alessandro (Frontiers in Pain Research, 2024)
IntroductionThis study aimed to assess the percentage of patients treated according to the European Society for Medical Oncology (ESMO) 2018 guidelines for breakthrough cancer pain (BTcP) and the impact of guidelines adherence on patients' quality of life (QoL).MethodsAdult opioid-tolerant patients diagnosed with BTcP and locally advanced or recurrent metastatic cancer with a life expectancy of >3 months prospectively were included. Patients were followed up for 28 days.ResultsOf 127 patients included, 37 were excluded due to the impossibility to establish adherence to the ESMO guidelines. Among the evaluable patients [51.1% female; with mean (SD) age of 66.4 (11.8) years], all were adherent. BTcP was diagnosed by the Association for Palliative Medicine algorithm in 47.8% of patients and by clinical experience in 52.2% of patients. The mean number of daily BTcP episodes ranged between 1 and 8, with a mean (95% CI) severity of 7.3 (7.0; 7.6) at week 0 and 6.2 (5.8; 6.6) at week 4. Time to maximum pain intensity was 3–15 min in 52.2% of patients, and BTcP lasted 30–60 min in 14.4% of patients at week 0 and 4.4% of patients at week 4. Mean (95% CI) treatment effectiveness was 6.6 (6.1; 7.1) at week 0 and 7.4 (7.0; 7.8) at week 4. Median (Q1–Q3) patients' global impression of clinical condition was 4.0 (4.0–4.0) at week 0 and 3.0 (2.0–3.0) at week 4.ConclusionA clear BTcP assessment and strict follow-up could be crucial to guidelines adherence and for patient's QoL.